Mechanism of Arctigenin-Induced Specific Cytotoxicity against Human Hepatocellular Carcinoma Cell Lines: Hep G2 and SMMC7721. - Zheng Lu; Shengbo Cao; Hongbo Zhou; Ling Hua; Shishuo Zhang; Jiyue Cao (PLoS ONE, 2015)
Arctigenin (ARG) has been previously reported to exert high biological activities including anti-inflammatory, antiviral and anticancer. In this study, the anti-tumor mechanism of ARG towards human hepatocellular carcinoma (HCC) was firstly investigated. We demonstrated that ARG could induce apoptosis in Hep G2 and SMMC7721 cells but not in normal hepatic cells, and its apoptotic effect on Hep G2 was stronger than that on SMMC7721. Furthermore, the following study showed that ARG treatment led to a loss in the mitochondrial out membrane potential, up-regulation of Bax, down-regulation of Bcl-2, a release of cytochrome c, caspase-9 and caspase-3 activation and a cleavage of poly (ADP-ribose) polymerase in both Hep G2 and SMMC7721 cells, suggesting ARG-induced apoptosis was associated with the mitochondria mediated pathway. Moreover, the activation of caspase-8 and the increased expression levels of Fas/FasL and TNF-α revealed that the Fas/FasL-related pathway was also involved in this process. Additionally, ARG induced apoptosis was accompanied by a deactivation of PI3K/p-Akt pathway, an accumulation of p53 protein and an inhibition of NF-κB nuclear translocation especially in Hep G2 cells, which might be the reason that Hep G2 was more sensitive than SMMC7721 cells to ARG treatment.